PENGARUH VARIASI TEGANGAN LISTRIK FUELPUMP YAMAHA VIXION TERHADAP EMISI GAS BUANG dan KONSUMSI BAHAN BAKAR - , AGUS ZAKI YAMANI, Ir.Andri Surjaka Isp., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The researcher attemps using motor vehicle exhaust gas emission rapidly developed and high of fuel consuming in society. Therefore, the aim of the research are to know content of exhaust gas emission from motor vehicle and level of fuel consuming. Yamaha Vixin 150 cc was a tool material that used in this experiment. One of innovation from this final duty was variation of fuel pump electric voltage. Electric voltage variations (10 V, 12 V and 14 V) were used to know the effect of electric voltage variation on fuel pump. The result of the experimentation shows that, the variation of electric voltage can be a comparison of exhaust gas emission with using three kinds of electric voltage. The variation of electric voltage can know level of fuel consuming. From the experiment, the researcher gets reduction data of fuel consuming at 10 volt and also get optimum reduction of exhaust gas emission in using10 Volt at2000rpm.